Advances in electron microscopy: a qualitative view of instrumentation development for macromolecular imaging and tomography - Schröder, Rasmus R. (Archives of biochemistry and biophysics, 2015)
Macromolecular imaging and tomography of ice embedded samples has developed into a mature imaging technology, in structural biology today widely referred to simply as cryo electron microscopy.1In the following I will strictly use the phrases ‘cryo electron microscopy’ and ‘cryo electron tomography’, even though I am well aware that there are no ‘cryo electrons’, and also that other authors use a different wording. Terms and abbreviations such as EM and ET have been in use for decades and it seemed to me more natural to add ‘cryo’ than to ignore the historically accurate ancestry of the techniques.1 While the pioneers of the technique struggled with ill-suited instruments, state-of-the-art cryo microscopes are now readily available and an increasing number of groups are producing excellent high-resolution structural data of macromolecular complexes, of cellular organelles, or the morphology of whole cells. Instrumentation developers, however, are offering yet more novel electron optical devices, such as energy filters and monochromators, aberration correctors or physical phase plates. Here we discuss how current instrumentation has already changed cryo EM, and how newly available instrumentation - often developed in other fields of electron microscopy - may further develop the use and applicability of cryo EM to the imaging of single isolated macromolecules of smaller size or molecules embedded in a crowded cellular environment.